2013
DOI: 10.1016/j.neuropharm.2012.09.022
|View full text |Cite
|
Sign up to set email alerts
|

New insights on neurobiological mechanisms underlying alcohol addiction

Abstract: Alcohol dependence/addiction is mediated by complex neural mechanisms that involve multiple brain circuits and neuroadaptive changes in a variety of neurotransmitter and neuropeptide systems. Although recent studies have provided substantial information on the neurobiological mechanisms that drive alcohol drinking behavior, significant challenges remain in understanding how alcohol-induced neuroadaptations occur and how different neurocircuits and pathways cross-talk. This review article highlights recent prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 144 publications
2
72
0
2
Order By: Relevance
“…The PVN and the BNST are involved in stress, emotion, and ethanol responses (Armario, 2010;Cui et al, 2012;Koob, 2013), and we have previously shown that ethanol increases cellular 3a,5a-THP in these regions (Cook et al, 2014). Previous studies have shown that GABAergic neuroactive steroids contribute to negative feedback on the HPA axis at the level of the hypothalamus in rats (Owens et al, 1992;Patchev et al, 1996;Patchev et al, 1994), and activate the stress response in the hypothalamus of C57BL/6J mice (Sarkar et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…The PVN and the BNST are involved in stress, emotion, and ethanol responses (Armario, 2010;Cui et al, 2012;Koob, 2013), and we have previously shown that ethanol increases cellular 3a,5a-THP in these regions (Cook et al, 2014). Previous studies have shown that GABAergic neuroactive steroids contribute to negative feedback on the HPA axis at the level of the hypothalamus in rats (Owens et al, 1992;Patchev et al, 1996;Patchev et al, 1994), and activate the stress response in the hypothalamus of C57BL/6J mice (Sarkar et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…128,189 Characterization of network changes via multiple modalities such as PET, fMRI, and diffusion tractography similarly elucidated possible sites for intervention in OCD. 43,109,182,212,226 Metabolic and functional imaging studies demonstrate network abnormalities in patients with Tourette syndrome (TS), 227 posttraumatic stress disorder (PTSD), 112 addiction, 46 and obesity. 71,153 Trials investigating the modulation of these targets with DBS for the treatment of psychiatric disease have followed.…”
Section: 54mentioning
confidence: 99%
“…Thus, we examined GABAergic and glutamatergic synaptic transmission in the striatum, a brain region known to be affected by ethanol exposure and self-administration (Wang et al, 2010;Cuzon Carlson et al, 2011;Cui et al, 2013;Depoy et al, 2013;Fanelli et al, 2013). Electrophysiological analyses showed that inhibitory GABAergic synapses are depressed following the DID treatment in both striatal subregions, DLS and DMS.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ethanol exposure affects brain pathways and neuronal circuits related to reward, stress (reviewed in Cui et al, 2013). Specifically, the dorsolateral (DLS) and dorsomedial striatum (DMS) are implicated in addiction (Koob and Volkow, 2010;Volkow et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation